Association of Knowledge and Attitudes with Sedentary Behavior Among Ninth-Grade Students at MTs Miftahul Umam - Isa Bella; safrudin; sri sukamti (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2026)
Background: Sedentary behavior is a lifestyle with minimal physical activity, characterized by the habit of sitting or lying down for a long time. Adolescents are one of the vulnerable groups experiencing sedentary behavior due to high screen time on technology use. Research Objective: To determine the relationship between students' knowledge and attitudes towards sedentary behavior at MTs Miftahul Umam in 2026. Research Method: This type of research is quantitative, with a cross-sectional design. The data collection technique used total sampling with a sample size of 65 respondents. The analysis used was the Chi-square test. Research Results: There is a relationship between gender (p = 0.001; OR = 9.922), age (p = 0.036; OR = 4.796), gadget ownership (p = 0.000; OR = 0.16), knowledge (p = 0.019; OR = 3.946) and attitudes (p = 0.000; OR = 13.778) with sedentary behavior. Conclusion: Sedentary behavior is influenced by gender, age, gadget ownership, knowledge, and attitudes. Therefore, interventions through health education are needed to support physical activity.